Transformation Of Police Language School As A Learning Organization With U-Theory Approach In Facing Globalization - Widyanto, Krisna Hadi; Jannah, Lina Miftahul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Globalization and the increasing trend of transnational crime require countries in the world to collaborate and cooperate with each other in dealing with the phenomenon of massive development of transnational crime. In relation to this, it requires Polri institutions to improve their foreign language competence in order to actively participate in their role in the international arena. With the demand for the development of Polri human resources to improve their language skills, the transformation of Sebasa Polri as a learning organization through the U-theory approach is a necessity that is relevant to contemporary conditions. This study aims to analyze the implementation of the transformation of Sebasa Polri as a learning organization using the U-theory approach to develop the human resources of teaching staff. The method used is a literature study to collect and analyze secondary data from reputable journals, government publications and related academic sources. The results of the study revealed that the application of U theory through the observing, presencing, and actuating stages can help Sebasa Polri in identifying the challenges of the conventional learning pattern system, building individual awareness and collective awareness, and implementing innovative strategies in educator development. The challenges that exist in the change focus on organizational culture resistance, limited resources, and lack of policy support from the leadership. Transformation as a learning organization has the potential to improve teaching effectiveness and optimize the capacity of human resources within the National Police, which in a broader role can strengthen the role of the National Police in preparing its personnel to face the challenges of globalization.